Efeito antioxidante e anti-inflamatório da nanopartícula de ouro na mucosite oral experimental - Vilar, Carmem Jane Ferreira (2020)
Oral mucositis is a side effect, frequent and debilitating in patients with head and neck cancer who are undergoing treatment with chemotherapy and radiotherapy. Characterized by ulcerative lesions in the oral mucosa, this pathology compromises the patient's well-being as well as limiting antitumor treatment. Since there are few protocols that have demonstrated effectiveness in preventing and treating this side effect, and knowing that in the literature there are several studies that demonstrate the antioxidant and anti-inflammatory role of the gold nanoparticle (NpAu), this study aims to evaluate the effect of NpAu on oral mucositis induced by 5-Flourouracil (5-FU), in hamsters studying signaling pathways. In this experimental model, the animals underwent intraperitoneal injection at the respective doses of 40 and 60 mg / kg on the 1st and 2nd days, and the right oral mucosa received mechanical trauma (TM) superficial grooves on the 4th day. The animals were euthanized on the 10th day of the experiment, and samples of the oral mucosa were subsequently collected. The experimental groups are composed of: polyvinylpyrrolidone (PVP), (TM) and (5-FU) (NpAu 62 or 125 or 250µg / kg). The parameters evaluated were: interleukin-1beta (IL-1β) and tumor necrosis factor (TNF-α) measurements performed by ELISA. Glutathione (GSH) was measured by spectrophotometry. Immunohistochemistry analyzes for nuclear factor kappa B (NF-kB) and cyclooxygenase-2 (COX-2) and gene expression for NAD (P) H quinone dehydrogenase (NQO1), heme oxygenase 1 (HMOX1) and ECH-associated protein 1 Kelch (KEAP1) by RT-PCR. The statistically significant results demonstrated that the levels of proinflammatory cytokines increased in the group of animals with untreated oral mucositis 5-FU, when compared with the group PVP: IL-1β (p <0.0001 vs. 5-FU), in the group of OM animals treated with 250µg / kg NpAu the levels of these cytokines were reduced when compared with the 5-FU group: IL-1β (p <0.001 vs. 5-FU), TNF-α (p <0.0001vs. 5-FU) and in the group of animals treated with NpAu 250µg / kg increased the levels of GSH when compared to the group 5-FU (p <0.0001 vs 5-FU). In immunohistochemistry for NF-kB, the group administered the 250 µg / kg NpAu dose demonstrated a significant reduction in immunostaining (score 2) when compared to the 5-FU group (* p <0.05 vs. 5-FU) and for COX-2 FU the same result (p <0.05 vs 5-FU). The analysis of gene expression of the NQO1, HMOX1 (p <0.0001 vs. 5-FU), and KEAP1 genes. Thus, it was demonstrated that the gold nanoparticle demonstrated an antioxidant and anti-inflammatory effect on oral mucositis induced by 5-FU in hamsters.